Validation of conducting wall models using magnetic measurements. (16th August 2016) - Hanson, J.M.; Bialek, J.; Turco, F.; King, J.; Navratil, G.A.; Strait, E.J.; Turnbull, A.
Abstract: The impact of conducting wall eddy currents on perturbed magnetic field measurements is a key issue for understanding the measurement and control of long-wavelength MHD stability in tokamak devices. As plasma response models have growth in sophistication, the need to understand and resolve small changes in these measurements has become more important, motivating increased fidelity in simulations of externally applied fields and the wall eddy current response. In this manuscript, we describe thorough validation studies of the wall models in themars-f andvalen stability codes, using coil–sensor vacuum coupling measurements from the DIII-D tokamak (Luxon et al 2005 Fusion Sci. Technol .48 807). Thevalen formulation treats conducting structures with arbitrary three-dimensional geometries, whilemars-f uses an axisymmetric wall model and a spectral decomposition of the problem geometry with a fixed toroidal harmonic n . The vacuum coupling measurements have a strong sensitivity to wall eddy currents induced by time-changing coil currents, owing to the close proximities of both the sensors and coils to the wall. Measurements from individual coil and sensor channels are directly compared withvalen predictions. It is found that straightforward improvements to thevalen model, such as refining the wall mesh and simulating the vertical extent of the DIII-D poloidal field sensors, lead to good agreement with the experimental measurements. In addition, couplings to multi-coil, n   =  1 toroidal mode perturbations are calculated from the measurements and compared with predictions from both codes. The toroidal mode comparisons favor the fully three-dimensional simulation approach, likely because this approach naturally treats n   >  1 sidebands generated by the coils and wall eddy currents, as well as the n   =  1 fundamental.